Shear-thinning hyaluronan-based fluid hydrogels to modulate viscoelastic properties of osteoarthritis synovial fluids. (6th June 2019) - Cai, Zhixiang; Zhang, Hongbin; Wei, Yue; Wu, Min; Fu, Ailing
Abstract : Hyaluronan-based injectable fluid hydrogel was prepared and used as an artificial synovial fluid for the treatment of osteoarthritis. Abstract : Hyaluronan (hyaluronic acid, HA) has been extensively explored as an attractive biomaterial for biomedical and pharmaceutical applications due to its unique physiological properties. In particular, HA is a major component of synovial fluid in normal knee joints and provides viscoelastic properties to synovial fluid. In osteoarthritic joints, synovial fluid loses its unique viscoelastic and lubrication properties. Intra-articular injection of HA in osteoarthritic knee joints is believed to restore viscoelasticity and lubrication abilities to synovial fluid. However, the main drawback of HA is its rapid degradation in synovial fluid. In order to overcome the problem of rapid clearance of HA, a HA-based hydrogel (vinyl sulfone-modified HA crosslinked by dithiol-terminated poly(ethylene glycol), HA-VS/SH-2-PEG) was synthesized in this study. Injectable fluid hydrogels (viscosupplements) possessing tunable viscoelasticity and controllable degradation rates were then prepared by adding HA-VS/SH-2-PEG microgels to HA solutions. The resultant viscosupplements exhibit enhanced viscoelastic properties, lubrication effects, efficient triamcinolone acetonide payload capacity, and high resistance to enzymatic degradation along with good biocompatibility and the capability to inhibit the progression of osteoarthritis in vivo . Overall, the results provide support for the use of injectable fluid hydrogels as a strategy for the treatment of osteoarthritis and potential for the clinical translation.